Avaliação dos níveis de anticorpos, citocinas e mirnas em pacientes com rinite mediada e não mediada por anticorpos IgE - Miranda, Juliana Silva (2015)
Allergic rhinitis with symptomatology and IgE (S-IgE+) is a classical disease with a pattern of inflammation of the upper airways well characterized by Th2 pathway regulation. However, the rhinitis with symptomatology triggered by house dust exposure and no systemic IgE (S-IgE-) is involved by an unknown IgE- independent mechanism, which is not well understood yet. The aims of this study were to investigate antibody responses to house dust mite (HDM) Dermatophagoides pteronyssinus (Dp), cytokine levels, relative expression of mRNA cytokines and microRNA (miRNA) in patients and control (CT) subjects. Three groups of subjects divided in S-IgE+ (n = 32), S-IgE- (n = 19), and CT (n = 31) by clinical symptoms, skin prick test (SPT) and levels of specific IgE to Dp were analyzed. Blood samples were collected and sera were used to measure IgG1, IgG3, IgG4, and IgA specific to crude Dp allergen extract by enzyme linked immunosorbent assay (ELISA). Peripheral blood mononuclear cells (PBMCs) from subjects (S-IgE+, 15; S-IgE-, 11; CT, 10) were isolated and stimulated with mitogen (phytohemagglutinin-PHA), crude Dp allergens extract, and medium alone for control. Supernatants were collected after 4 days to evaluate the cytokine levels, and cells were harvested for RNA extraction to assess the relative expression of cytokines and miRNA by reverse transcription PCR (RT-qPCR). Specific IgE and IgG4 anti- Dp showed seropositivity rate significantly higher in S-IgE+ than S-IgE- or CT subjects. Specific IgG3 to Dp showed significant higher levels in S-IgE+ than CT group. Levels of Dpspecific IgA and IgG1 showed no significant difference among the groups. The cytokine IL-5 was significantly higher in cell culture supernatants after Dp stimulation from S-IgE+ patients than S-IgE- or CT subjects. However, levels of IL-4, IL-10, IL-13, IL-17 and IFN-γ were not significantly different among groups, as well as the cytokine levels in sera, including IL-5. Relative expression of IL-5, IFN-γ and TGF-β in PBMCs stimulated with Dp allergens showed significant values, with higher levels of IL-5 in S-IgE+ compared to S-IgEand CT groups; IFN-γ showed higher expression in S-IgE+ when compared to CT; and TGF-β presented higher expression in S-IgE- group. miRNAs relative expression was similar among groups. In the overall, our data suggested that S-IgE- patients showed serum antibodies, cytokines in the supernatant of the cell culture stimulated with Dp allergens and in sera more similar to CT individuals than to S-IgE+, although the symptoms in S-IgE- patients were triggered after house dust exposure like S-IgE+ patients, demonstrating that the mechanism of the antibody and cytokine responses are quite different between S-IgE- and SIgE+ groups. In addition, the relative expression of IL-5, IFN-γ and TGF-β was quite different of seen in cytokine levels measure, explained by the difference between the relative expression of gene and its protein. For miRNA in PBMCs stimulated with Dp allergens were not significantly different among the three groups, and a reason could be the small sample tested. Our findings showed that antibody, cytokine and miRNAs profiles analyzed in this study were not able do discriminate these groups, additional studies will be needed for elucidation of the real immunopathogenic mechanisms of this complex S-IgE- group of patients.